2022
DOI: 10.1016/j.jmig.2021.08.009
|View full text |Cite|
|
Sign up to set email alerts
|

The Comparison of Transvaginal Natural Orifice Transluminal Endoscopic Surgery and Conventional Laparoscopy in Opportunistic Bilateral Salpingectomy for Permanent Female Sterilization

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 32 publications
3
19
0
Order By: Relevance
“…We previously performed a propensity-matched analysis [14] and found that total operative is similar comparing trans- vaginal and PSSR after LM, although retrieval time was lower in the first group; in addition, blood loss and complication rate have been found similar between the two groups; finally, pain was lower in transvaginal group compared port-site group. Interestingly, these elements are in line with the results of several recent studies about transvaginal natural orifice transluminal endoscopic surgery, confirming that this technique is associated with better cosmesis, less trocar-related complications, and less pain scores compared with conventional laparoscopy [25][26][27].…”
Section: Discussionsupporting
confidence: 83%
“…We previously performed a propensity-matched analysis [14] and found that total operative is similar comparing trans- vaginal and PSSR after LM, although retrieval time was lower in the first group; in addition, blood loss and complication rate have been found similar between the two groups; finally, pain was lower in transvaginal group compared port-site group. Interestingly, these elements are in line with the results of several recent studies about transvaginal natural orifice transluminal endoscopic surgery, confirming that this technique is associated with better cosmesis, less trocar-related complications, and less pain scores compared with conventional laparoscopy [25][26][27].…”
Section: Discussionsupporting
confidence: 83%
“…According to previous studies, the suggested time of starting sexual life is 2 weeks after surgery [27][28][29][30]. However, some studies also indicate that it takes longer to start sexual life after vNOTES.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, the time for each patient to start sexual life after surgery is different. A prospective cohort study by Yassa M et al [27] shows that 75% of patients undergoing vNOTES bilateral salpingectomy have sexual activity during the one-month period of follow-up, with no complications caused by sexual activity. A Japanese study [32] performed a retrospective analysis of transvaginal ovarian cystectomy (conventional vaginal surgery or vNOTES) and found that the median time for patients to start sexual life after surgery was 2 months, ranging from 1 month to 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…This prospective study evaluated 96 participants and reported that the rate of patients reporting postoperative decline in FSFI pain scores (relative risk [RR], 0.97; 95% confidence interval [CI], 0.47-1.96) was found to be similar in both study groups. 16 Another retrospective study of patients with severe prolapse who underwent vNOTES for uterosacral ligament suspension following vaginal hysterectomy concluded that the pelvic organ prolapse/urinary incontinence sexual questionnaire score was significantly increased after surgery, indicating notable improvement in quality of sexual life. 17 The strengths of this study are its prospective randomized design, utilization of the VAS system with an additional rescue analgesia parameter for pain assessment, and the FSFI questionnaire for sexual health assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Yassa et al compared vNOTES approach with conventional laparoscopy in opportunistic bilateral salpingectomy alone for permanent female sterilization. This prospective study evaluated 96 participants and reported that the rate of patients reporting postoperative decline in FSFI pain scores (relative risk [RR], 0.97; 95% confidence interval [CI], 0.47–1.96) was found to be similar in both study groups 16 . Another retrospective study of patients with severe prolapse who underwent vNOTES for uterosacral ligament suspension following vaginal hysterectomy concluded that the pelvic organ prolapse/urinary incontinence sexual questionnaire score was significantly increased after surgery, indicating notable improvement in quality of sexual life 17 .…”
Section: Discussionmentioning
confidence: 99%